Comparative analysis of protocols for decellularization of corneal lenticular tissue - S. A. Borzenok; S. V. Kostenev; A. V. Doga; A. V. Shatskikh; V. G. Li; D. S. Ostrovskiy; M. K. Khubetsova (Вестник трансплантологии и искусственных органов, 2021)
Shortage of donor corneas is a burning issue in ophthalmology. That is why there is a search for new alternative ways for treating corneal diseases. Decellularization technologies make it possible to create corneal tissue-engineered constructs that can adrress the issue of donor corneal shortage. Objective: to conduct a comparative analysis of effective methods for treating the corneal lenticula and to create an optimized and standardized decellularization protocol. Materials and methods. Corneal stromal lenticules obtained after ReLEx SMILE surgery were chosen for the study. Lenticule parameters: thickness 77–120 microns, diameter 6.5 mm. We used 3 protocols for the treatment of lenticules: 1) treatment with 1.5 M sodium chloride with nucleases (NaCl); 2) 0.1% SDS (SDS); 3) treatment with Trypsin-EDTA solution, followed by double washing in a hypotonic Tris buffer solution with nucleases (Trypsin-EDTA). Optical properties of lenticles were determined spectrophotometrically, where the samples before decellularization served as a control. Fluorescence imaging of nuclear material in the original cryosections was performed using Hoechst dye. The state of collagen fiber ultrastructure was assessed by scanning electron microscopy. The quantitative DNA content in fresh lenticules and in lenticules after treatment was analyzed. Results. All three decellularization protocols effectively removed nuclear and cellular material; the residual DNA content was < 50 ng/mg. However, the Trypsin-EDTA protocol led to significant damage to the extracellular matrix structure, which negatively affected the transparency of corneal tissue-engineered constructs. Transparency of samples for the NaCl protocol was close to native lenticules. Conclusion. To create a corneal tissue-engineered construct, NaCl decellularization protocols appear to be optimized and can be used to treat various corneal diseases.